Weder Staat noch Kollektiv: Sozialismuskritik im Werk von Karl Marx - Wallat, Hendrik (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2009)
Even Marx had never written a systematical critique of other socialism's, his whole work is full of commentaries about various forms of them, On the one hand Marx's critical notes are directed against anti-individualistic, authoritarian and etatist conceptions of human emancipation, on the other hand they focus doctrines which perpetuate capitalistic modes of production and social synthesis,